Modeling Solar-Wind Hybrid Energy System Using MATLAB Simulink - Zaheruddin, Muhammad Alief; Jumaat, Siti Amely (Evolution in Electrical and Electronic Engineering, 2023)
Renewable energy sources like solar and wind can be used to generate electricity. As indicated in the 9th Malaysian Plan, the Malaysian government has stated its interests in and commitment to expanding the renewable energy sector. Intermittent energy sources include solar and wind. Implementing a hybrid system, in which the solar and wind plants complement one another to further improve their ability to capture energy, can increase the dependability and overall performance of solar and wind power plants. This presents a model of a hybrid solar-wind energy system using MATLAB Simulink. The main goal of this project is to model the wind and solar energy system using MATLAB Simulink and evaluate the performance of the solar wind system. To further enhance the hybrid system’s overall performance, elements affecting solar-powered systems’ efficiency were researched in addition to combining both power sources. The location of the project is Kuala Terengganu as Kuala Terengganu has the potential to develop a hybrid solar-wind energy system. The first development of the modeling equations for sizing simulations took place during the theoretical development stage. From the simulation, the result for solar energy based on the number of solar panels is 52 solar panels and the wind energy based on the area of blades for wind turbines is 284.9 m2. In conclusion, the findings of this study contain manual calculations performed for wind energy and solar energy to get the system size of the solar system and wind turbine.